Assessing the effect of E-Bayesian inference for Poisson inverse exponential distribution parameters under different loss functions and its application. Issue 17 (2nd September 2022) - Pathak, Anurag; Kumar, Manoj; Singh, Sanjay Kumar; Singh, Umesh
Abstract: This paper present E-Bayesian and Bayesian estimators of parameters of Poisson inverse exponential distribution ( PIED ) under Squared error loss function (SELF), General entropy loss function (GELF) and Linear Exponential loss function (LINEX) for progressive type-II censored data with binomial removals (PT-II CBRs). The E-Bayesian and corresponding Bayesian estimators are compared in terms of their risks based on simulated samples from PIED . The proposed methodology is applied to survival time of multiple myeloma patients data.